2007
DOI: 10.1159/000104871
|View full text |Cite
|
Sign up to set email alerts
|

The Endothelial Glycocalyx Prefers Albumin for Evoking Shear Stress-Induced, Nitric Oxide-Mediated Coronary Dilatation

Abstract: Background: Shear stress induces coronary dilatation via production of nitric oxide (NO). This should involve the endothelial glycocalyx (EG). A greater effect was expected of albumin versus hydroxyethyl starch (HES) perfusion, because albumin seals coronary leaks more effectively than HES in an EG-dependent way. Methods: Isolated hearts (guinea pigs) were perfused at constant pressure with Krebs-Henseleit buffer augmented with 1/3 volume 5% human albumin or 6% HES (200/0.5 or 450/0.7). Coronary flow was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 65 publications
2
45
0
5
Order By: Relevance
“…Increased endothelial shear increases nitric oxide (NO) production, which in turn dilates vessels and reduces stress [18]. Human umbilical vein endothelial cells stressed by shear double the amount of hyaluronic acid in the glycocalyx -a second mechanism through which shear could be controlled [9].…”
Section: Physiology Of the Endothelial Surface Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Increased endothelial shear increases nitric oxide (NO) production, which in turn dilates vessels and reduces stress [18]. Human umbilical vein endothelial cells stressed by shear double the amount of hyaluronic acid in the glycocalyx -a second mechanism through which shear could be controlled [9].…”
Section: Physiology Of the Endothelial Surface Layermentioning
confidence: 99%
“…Albumin attenuated glycocalyx shedding during 4 h of cold ischaemia and reperfusion in guinea pig hearts, reducing interstitial oedema and intracoronary adhesion of leucocytes [40]. Albumin dilates coronary arteries compared with HES, possibly by enhancing NO production in response to shear stress: vasodilation by albumin was reduced when NO synthase was blocked and when the glycocalyx was damaged [18]. Fresh frozen plasma reduces glycocalyx damage and facilitated its restoration in rodent haemorrhagic shock [41].…”
Section: Damage To the Endothelial Surface Layermentioning
confidence: 99%
“…Recent studies have found glycocalyx deficiency when the ECs are cultured in vitro [50,51]. Damiano E R. et al showed that the glycocalyx thickness of in vitro cultured human umbilical vein was 0.03 m under standard cell culture conditions, c.a.…”
Section: Discussion Of Ecs Gel Friction In Vitro Using Hydrogel Lubrimentioning
confidence: 99%
“…These are normally hidden deep within the glycocalyx structure, but become exposed following damage to the EGL [36 • ]. It also protects the vascular endothelium from shear stress and oxidative damage, via nitric oxideinduced vasodilation [37] and scavenging of oxygen free radicles [35].…”
Section: Revised Starling Equation and The Endothelial Glycocalyxmentioning
confidence: 99%